Pass it on - Sadler, Marilyn (Blue Apple Books, 2012)
Bee's friend Cow is stuck in a fence and asks for his help, so Bee tells Frog about Cow's predicament and asks him to "Pass it on!", causing a series of misunderstandings that, at last, brings the help Cow needs.